Chinese Neonatal Network: a national protocol for collaborative research and quality improvement in neonatal care. Issue 5 (2nd May 2022) - Hei, Mingyan; Li, Xiaoying; Shi, Yuan; Cao, Yun; Sun, Jianhua; Wu, Hui; Jiang, Siyuan; Ma, Xiaolu; Wang, Yanchen; Sun, Huiqing; Zhang, Huayan; Du, Li-Zhong; et al.
Abstract : Introduction: The objective of the Chinese Neonatal Network (CHNN) is to provide a platform for collaborative research, outcomes evaluation and quality improvement for preterm infants with gestational age less than 32 weeks in China. The CHNN is the first national neonatal network and has the largest geographically representative cohort from neonatal intensive care units (NICUs) in China. Methods and analysis: Individual-level data from participating NICUs will be collected using a unique database developed by the CHNN on an ongoing basis from January 2019. Data will be prospectively collected from all infants <32 weeks gestation or <1500 g birth weight at 58 participating NICUs. Infant outcomes and inter-institutional variations in outcomes will be examined and used to inform quality improvement measures aimed at improving outcomes. Information about NICU environmental and human resource factors and processes of neonatal care will also be collected and analysed for association with outcomes. Clinical studies, including randomised controlled trials will be conducted using the CHNN data platform. Ethics and dissemination: This study was approved by the ethics review board of Children's Hospital of Fudan University, which was recognised by all participating hospitals. Waiver of consent were granted at all sites. Only non-identifiable patient level data will be transmitted and only aggregate data will be reported in CHNN reports and publications.